IMPLEMENTASI METODE KRIPTOGRAFI ADVANCED ENCRYPTION STANDARD 128 BIT (AES 128 BIT) PADA KEAMANAN FILE DOKUMEN - Setiawan , Danang; Mufarrihah , Iftitaahul (Inovate, 2024)
The confidentiality of data is a highly valuable asset and must be safeguarded from unauthorized parties. This is especially crucial for confidential document data. If important document data goes missing and is misused by irresponsible individuals, it can cause harm to the party that possesses the data. Therefore, research is conducted with the aim of creating a system that can secure data by encrypting and decrypting document data in file formats (PDF, DOC, XLS, and TXTusing the AES 128-bit encryption and decryption method. The result of this research will produce encrypted Document Files in the form of ciphertext containing hexadecimal values. There is minimal change between the original file and the decrypted file, ensuring that securing document data with the AES 128-bit method is safe and reliable. Keywords: Document Files, Encryption, Decryption, AES-128 Bit..